Effective Government Management of Flood Discharge in Drainage Channels using HEC-RAS 6.3.1 Application - Nathanael, Estha; Sejati, Wahyu (Pandawan, 2023)
Flooding remains one of the most significant natural disasters affecting communities around the world. Proper management of flood discharge in drainage channels is essential to mitigate its impacts on public safety, infrastructure, and the environment. In recent years, advancements in hydrodynamic modeling tools, such as the Hydraulic Engineering Center's River Analysis System (HEC-RAS) 6.3.1, have provided governments with powerful tools to analyze and manage flood discharges effectively. This research aims to investigate the role of government-led management strategies in handling flood discharge within drainage channels using the HEC-RAS 6.3.1 application. The study assesses how the application's features and capabilities can be harnessed by governmental agencies to make informed decisions and implement effective flood management plans. The research methodology involves a combination of field surveys, data collection, and computer simulations using the HEC-RAS 6.3.1 software. Geographic information systems (GIS) data, topographical surveys, and historical flood records are utilized to calibrate and validate the model's accuracy. Various flood scenarios are simulated to assess the performance of different government-led management strategies. The findings of this study reveal that the integration of HEC-RAS 6.3.1 with government-led management approaches enhances the understanding of flood dynamics within drainage channels. The application facilitates the identification of critical flood-prone areas, prediction of potential flood events, and evaluation of flood mitigation measures. The government can utilize this valuable information to formulate more effective flood management policies and allocate resources efficiently.